2014
DOI: 10.5936/csbj.201403003
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and Migration of Murine Cd4 Single Positive Thymocytes and Thymic Emigrants

Abstract: T lymphopoiesis in the thymus was thought to be completed once they reach the single positive (SP) stage, when they are “fully mature” and wait to be exported at random or follow a “first in-first out” manner. Recently, accumulating evidence has revealed that newly generated SP thymocytes undergo further maturation in the thymic medulla before they follow a tightly regulated emigrating process to become recent thymic emigrants (RTEs). RTEs in the periphery then experience a post-thymic maturation and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 132 publications
0
6
0
Order By: Relevance
“…However, recent studies have revealed that newly generated SP thymocytes undergo further developmental programme in the thymic medulla before they follow a tightly regulated emigrating process to become RTEs . We detected TRECs to determinate RTEs that is often used as a marker to predict the status of thymopoiesis . As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…However, recent studies have revealed that newly generated SP thymocytes undergo further developmental programme in the thymic medulla before they follow a tightly regulated emigrating process to become RTEs . We detected TRECs to determinate RTEs that is often used as a marker to predict the status of thymopoiesis . As shown in Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Following maturation, thymocytes exist in the thymus as latestage thymocytes before they egress the thymus as recent thymic emigrants (32). To assess a possible role for coronin 1 at later developmental stages, the levels of cell surface markers that define this cell population, in particular CD62L, Qa2, and CD24, were assessed.…”
Section: Resultsmentioning
confidence: 99%
“…Thymocytes will then differentiate into single-positive CD4 + T cells or CD8 + T cells if they respond to MHC-II or MHC-I molecules, respectively [93]. Upon single-positive selection, these thymocytes migrate to secondary locations such as the spleen and lymph nodes [94, 95]. The increase in single-positive CD8 + thymocytes following oxaliplatin may suggest the enhanced recruitment of cytotoxic T cells to the periphery.…”
Section: Discussionmentioning
confidence: 99%